Unaware and unpowered: evaluating patient perceptions and preferences of biosimilars in South Korea - Choi, Eunjung; Shin, Gyeongseon; Bae, SeungJin (Frontiers in Pharmacology, 2025)
ObjectivesBiosimilars offer a promising solution to challenges related to healthcare budget sustainability. However, limited patient awareness and understanding often hinder their timely adoption. This cross-sectional survey evaluates the perceptions, preferences, and experiences of South Korean patients regarding biosimilars.MethodsAn anonymous, self-administered, web-based survey comprising up to 26 questions was conducted. Participants were recruited from Ewha Womans University Medical Centers from November 2023 to August 2024. The analysis focused on respondents with medical conditions typically treated with biologics, such as solid tumors, blood cancers, and autoimmune diseases.ResultsOut of 133 responses, 100 were analyzed after excluding 33 individuals with irrelevant medical conditions. Among these, 66% had heard of biosimilars, primarily through the internet (28.8%, 19 out of 66). However, 55% were unfamiliar with the definition of biosimilars, and 61% did not understand the difference between generics and biosimilars. While most respondents considered biosimilars comparable to originators in terms of safety (45%) and efficacy (41%), the primary concerns were a lack of confidence in their safety (50%) and efficacy (50%). Among patients who exclusively used either originators or biosimilars, 91.7% and 95%, respectively, cited their doctors’ recommendations as the main reason for choosing their treatment.ConclusionPatients primarily rely on doctors’ recommendations, yet their awareness and understanding of biosimilars remain limited. To enhance positive perceptions of biosimilars among patients, implementing diverse educational programs and actively involving a multidisciplinary health team is essential. Such initiatives will not only increase patient access to these treatments but also contribute to the long-term sustainability of healthcare systems by encouraging the broader adoption of biosimilars.